Marketing Communications in the Environment and Awareness of Sustainable Development - Tripunoska, Maya; Tripunoski, Mirko; Sibinovski, Borce (Research Papers, 2021)
Environmental marketing communications and awareness-raising for sustainable development, monitoring and data management are interconnected. They cannot be divided and managed independently. The development of a strategy for each of them must take into account their interactions. Communication is therefore a broad spectrum of information exchange. The perception of the transmitted information depends on the subject and its proper presentation. From here, the information in this paper is not a missing tool between a problem and its solution, where what is said does not mean heard, hearing does not mean understood, understood does not mean accepted and accepted does not mean done. For these reasons marketing communication in the environment must be a planned and strategically utilized process of communication of mutual products containing effective policy, public participation and project implementation for sustainable development.